THE GROWTH OF SHOOT CUTTINGS FROM COPPICE SHOOTS OF Eucalyptus pellita F. Muell. SEEDLINGS AR THE NURSERY - Hamdan Adma Adinugraha; Sugeng Pudjiono; Dhanang Yudistiro (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2007)
The aim of the experiment was to investigate to success rate of shoot cuttings on by different media and the height of hedging of Eucalyptus pellita F. Muell seedlings. The experiment was arranged in completely randomized design with two factors. The first factor was media compound, consists of 3 levels: sand, coconut husk and mixture of sand +coconut husk (1:1). The second factor was the height of hedging, consist of 4 levels : 5 cm, 10 cm, 15 cm, and 20 cm above the ground. The result showed that the effect the treatment was significantly affected the success rate of the shoot cuttings. The cuttings from seedlings, which hedged at 15 cm above ground showed the best result. The media that gave the best rooting success was sand river. The average of rooting percentage was 15 - 95%, shoot length was 0,45 cm - 6,29 cm, shoot dry weight was 0,005 g - 0,049 g and volume of root was 0,020 ml - 0,123 ml.